Are Leukocyte and Platelet Abnormalities and Complete Blood Count Ratios Potential Prognostic Markers in Canine Sepsis? - Pierini, Alessio; Gori, Eleonora; Lippi, Ilaria; Lubas, George; Marchetti, Veronica (Frontiers in Veterinary Science, 2020)
Background: Sepsis is a common disease in which early diagnosis and prognosis assessment are the main aims in order to arrange a prompt and effective treatment. Objectives: (1) To compare leukogram parameters (WBC, segmented and band neutrophils, lymphocytes, monocytes), platelet count (PLT), mean platelet volume (MPV), and some leukocyte/platelet ratio such as NLR, NBNLR, PLR and MLR between dogs with systemic inflammatory response syndrome (SIRS) and sepsis. (2) To investigate any difference in the trend of these latter parameters between survivors and non-survivors septic dogs. Animals: 57 dogs with confirmed sepsis and 57 dogs with non-septic SIRS. Methods: A review of the medical records was conducted in order to find dogs with sepsis. Sepsis was defined as the presence of an infectious focus with fulfillment of systemic inflammatory response syndrome criteria (SIRS). Septic dogs had to have a CBC at admission and another CBC within 48h from the previous timepoint. Purebreds with CBC breed-related abnormalities were excluded, together with dogs without confirmed sepsis and dogs with only a single CBC. NLR, NBNLR, PLR and MLR were calculated. Univariate analysis of all blood parameters studied was assessed between SIRS and septic dogs. Generalized Estimating Equations models for repeated measures were used to test if the blood parameters studied were modified between survivors and non-survivors in the septic group. Results: Septic dogs had lower median segmented neutrophils count and NLR compared to SIRS dogs (p = 0.02 and p = 0.04, respectively). Lastly, septic dogs had a higher prevalence of toxic neutrophil than SIRS dogs (p = 0.01). We found that for a 1-unit increase of PLR and MLR, the risk of death increased by 50.5% and 60%, respectively. Conclusion and clinical importance: Evaluation of NLR at hospital admission may be a useful marker of inflammation, although it showed low sensitivity in differentiating SIRS and septic dogs. The monitoring of some CBC parameters, especially PLR and MLR may be useful in the establishment of prognosis in septic dogs.